The Effectiveness of Fiscal Policy Over the Business Cycle: A CEE Perspective. Issue 8 (2nd August 2016) - Baranowski, Paweł; Krajewski, Piotr; Mackiewicz, Michał; Szymańska, Agata
ABSTRACT: In this article we analyze the effectiveness of fiscal policy—for a group of four Central and Eastern European countries. The recent literature shows that fiscal multipliers in the developed economies are higher during recession than expansion. So far, similar empirical analyses have been lacking for CEE countries. The results presented in this article show that fiscal multipliers in CEE countries differ with respect to the phase of the business cycle. Based on the SVAR methodology in which we allow for deterministic regime switching, we show that the government spending multipliers are significantly higher when the output gap is negative.